Сучасний стан, проблеми і перспективи розвитку вугільної промисловості України - Lyashenko O.F. (General Energy Institute of the National Academy of Sciences of Ukraine, 2003)
Evaluations of a present condition of a coal industry in Ukraine are executed on basis of retrospective analysis of technological parameters of branch operation. The influence of the factors causing it is researched. The prime measures in order to increase the branch operation effectiveness are suggested.